2011
DOI: 10.3113/fai.2011.0789
|View full text |Cite
|
Sign up to set email alerts
|

Peroneal Tenography to Evaluate Lateral Hindfoot Pain after Calcaneal Fracture

Abstract: Calcaneal widening following fracture union was the cause of compression of the peroneal tendons. Increasing compression correlated with increasing levels of lateral pain. Our study demonstrated the utility of peroneal tenography in identifying the presence of peroneal tendon impingement in patients with lateral pain following calcaneal fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Calcaneal fractures are devastating injuries with relatively poor outcomes depending on the fracture pattern. Combined in the setting of the missed traumatic superior peroneal retinacular injury with subluxation, the morbidity can be signifi cant (7)(8)(9). Poor outcomes specifi cally pertaining to this have been reported specifi cally relating to the inability to resist inversion due to peroneal tenosynovitis.…”
Section: Discussionmentioning
confidence: 99%
“…Calcaneal fractures are devastating injuries with relatively poor outcomes depending on the fracture pattern. Combined in the setting of the missed traumatic superior peroneal retinacular injury with subluxation, the morbidity can be signifi cant (7)(8)(9). Poor outcomes specifi cally pertaining to this have been reported specifi cally relating to the inability to resist inversion due to peroneal tenosynovitis.…”
Section: Discussionmentioning
confidence: 99%
“…The imaging results showed that the calcaneal width of the PR group was larger than that of the STA group postoperation and during follow-up. Studies have shown that widening of the calcaneus is the main cause of lateral impingement syndrome 33,34 . In this study, as for the lateral impact of the calcaneus, there were 3 cases in the PR group and 2 cases in the STA group.…”
Section: Comparison and Significance Of Radiological Imagesmentioning
confidence: 99%
“…Reviewing the axial and coronal CT images using Ho et al criteria is suggested. It is also worth mentioning that CT scans may overestimate the prevalence of peroneal tendon dislocation; hence, intraoperative assessment of peroneal tendon stability is paramount for proper management [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The recommended examination technique by Chen et al is to introduce a Freer elevator within the peroneal tendon sheath followed by application of anterior and lateral forces. Any advancement over the anterior border of the fibula is diagnostic [10]. An anterolateral approach may also be utilized by making an incision in line with the fourth ray between the tibia and fibula, just lateral to the extensor digitorum longus; however, this approach is not ideal for tackling the peroneal tendons.…”
Section: Discussionmentioning
confidence: 99%